The Network of Inflammatory Mechanisms in Lupus Nephritis - Nozaki, Yuji (Frontiers in Medicine, 2020)
Several signaling pathways are involved in the progression of kidney disease in humans and in animal models, and kidney disease is usually due to the sustained activation of these pathways. Some of the best understood pathways are specific proinflammatory cytokine and protein kinase pathways (e.g., protein kinase C and mitogen-activated kinase pathways, which cause cell proliferation and fibrosis and are associated with angiotensin II) and transforming growth factor-beta (TGF-β) signaling pathways (e.g., the TGF-β signaling pathway, which leads to increased fibrosis and kidney scarring. It is thus necessary to continue to advance our knowledge of the pathogenesis and molecular biology of kidney disease and to develop new treatments. This review provides an update of important findings about kidney diseases (including diabetic nephropathy, lupus nephritis, and vasculitis, i.e., vasculitis with antineutrophilic cytoplasmic antibodies). New disease targets, potential pathological pathways, and promising therapeutic approaches from basic science to clinical practice are presented, and the blocking of JAK/STAT and TIM-1/TIM-4 signaling pathways as potential novel therapeutic agents in lupus nephritis is discussed.